Artemether-lumefantrine versus pyronaridine-artesunate for the treatment of malaria in patients with mild to moderate COVID-19 in Kenya and Burkina Faso: a randomised open-label trial (MALCOV). - Tangara,B; Barsosio,HC; Marlais,T; Kabore,JMT; Tiono,AB; Otieno,K; Wanjiku,M; Achieng,M; Onyango,ED; Ondieki,ED; Aura,H; Odawo,T; et al. (EClinicalMedicine, 2026)
BACKGROUND: It is unknown whether the choice of malaria treatment for uncomplicated malaria affects coronavirus disease 2019 (COVID-19) severity, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) viral load, or duration of viral shedding. Several antimalarials exhibit antiviral activity against SARS-CoV-2 in vitro and have been suggested as potential therapeutic candidates for COVID-19, particularly pyronaridine-artesunate (PA), despite disappointing clinical results with chloroquine and hydroxychloroquine. METHODS: We conducted an open-label randomised trial comparing standard 3-day treatment with PA and artemether-lumefantrine (AL) in newly diagnosed SARS-CoV-2 infected patients aged ≥6 months with rapid diagnostic test or microscopy-confirmed non-severe malaria in Kenya and Burkina Faso. SARS-CoV-2 was assessed by RT-PCR on days 3, 7, 14, and 28, and symptom resolution was assessed daily for 14 days using FLU-PRO Plus. The primary endpoint was the proportion of participants with SARS-CoV-2 clearance by day 7. Secondary endpoints included SARS-CoV-2 clearance by days 14, 21, and 28, time to SARS-CoV-2 clearance over 28 days, median viral load on day 7, and time to symptom resolution. Complete case analysis was conducted using log-binomial regression for binary outcomes, Cox-regression for time-to-event outcomes, and negative binomial regression for count outcomes, all adjusted for disease severity and viral load at enrolment. The trial is registered with ClinicalTrials.gov NCT04695197. FINDINGS: From January 2021 to January 2022, 143 participants were randomised (PA = 69, AL = 74, intention-to-treat [ITT] population), including 117 with reverse transcription polymerase chain reaction (RT-PCR) confirmed (PA = 58, AL = 59, modified intention-to-treat [mITT] population) and 26 with rapid-antigen test confirmed SARS-CoV-2 infection. The median age was 19 years (interquartile range [IQR] 13-38), 66% were aged ≥15 years. Baseline characteristics were co